Shaky foundations : the politics-patronage-social science nexus in Cold War America - Solovey, Mark, 1964- (Studies in modern science, technology, and the environment., 2013)
Shaky Foundations provides the first extensive examination of a new patronage system for the social sciences that emerged in the early Cold War years and took more definite shape during the 1950s and early 1960s. Focusing on the defense department, the Ford Foundation, and the National Science Foundation, Mark Solovey explores the struggles of these various funders to define what counted as legitimate social science and how their policies and programs helped to shape the goals, subject matter.